Analisis Penerapan Media Pembelajaran Wordwall Dalam Pembelajaran Informatika - Luluk Kusfiah Nurvania (Lembaga Pengembangan Kinerja Dosen, 2025)
Rapid technological developments require technology integration in learning. Developing science and technology from an early age is one of the best approaches in the context of education in the era of globalization. Informatics subjects have been implemented in the Indonesian curriculum to ensure students' ability to use technology. Interactive learning media plays an important role in strengthening students' understanding of complex concepts. Conventional learning paradigms can be changed to be more interesting, collaborative, and relevant if used in education. One interesting learning media is Wordwall, an application that offers various game features to increase students' interest and motivation to learn. In the context of informatics learning in junior high schools, the use of Wordwall can be an effective alternative to help students remember the components of a computer system. In order to support the use of Wordwall in learning, a literature study was conducted to understand more deeply about the use of this application and the factors that influence it. This study applies the literature study method by collecting and analyzing several related references in the last 5-10 years to present relevant and up-to-date information. By evaluating the results of previous studies, we can conclude that the use of Wordwall in education promises significant progress in student learning outcomes and motivation.